2021
DOI: 10.7150/jca.58524
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of TMEFF1 in Endometrial Carcinoma and the Mechanism Underlying its Promotion of Malignant Behavior in Cancer Cells

Abstract: Background: Although tomoregulin-1 (TMEFF1) is involved in embryonic development and central nervous system regulation and is a cancer suppressor gene in brain cancers, its role in endometrial carcinoma remains unclear. Methods: The expression and prognostic value of TMEFF1 were analyzed by bioinformatics methods and immunohistochemistry. An endometrial carcinoma cell line with low expression of TMEFF1 was constructed. Scratch and Transwell assays were used to determine the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…High TMEFF1 expression has been detected in melanoma, liver cancer, and kidney cancer cell lines [ 9 ], but there have been no functional studies. We confirmed that TMEFF1 is an oncogene in ovarian cancer and endometrial carcinoma [ 10 , 49 ]. TMEFF1 promotes cell proliferation, migration and invasion, inhibits apoptosis through MAPK and PI3K/AKT signaling pathways [ 10 ], and interacts with the tumor marker protein AHNAK in ovarian cancer [ 20 ].…”
Section: Discussionsupporting
confidence: 71%
“…High TMEFF1 expression has been detected in melanoma, liver cancer, and kidney cancer cell lines [ 9 ], but there have been no functional studies. We confirmed that TMEFF1 is an oncogene in ovarian cancer and endometrial carcinoma [ 10 , 49 ]. TMEFF1 promotes cell proliferation, migration and invasion, inhibits apoptosis through MAPK and PI3K/AKT signaling pathways [ 10 ], and interacts with the tumor marker protein AHNAK in ovarian cancer [ 20 ].…”
Section: Discussionsupporting
confidence: 71%
“…TMEFF1 is highly expressed in endometrial cancer and is closely related to FIGO staging and lymph node metastasis. Interference with TMEFF1 inhibits the invasion, migration and EMT progress of endometrial cancer cells [ 27 ]. Butorphanol treatment suppressed the viability, migration, invasion and colony formation of ovarian cancer cells, and it was found that Butorphanol might play its role by decreasing TMEFF1 expression [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mitogen-activated protein kinase (MAPK) pathway is a complex signal cascade that is often involved in tumorigenesis, tumor progression and drug resistance [ 30 ]. According to reports, TMEFF1 can promote the malignant behaviors of ovarian cancer and endometrial cancer cells by activating MAPK and PI3K/AKT signaling pathways [ 18 , 27 ]. Our data demonstrated that interference with MIR503HG activated the MAPK and PI3K/AKT signaling pathways, while TMEFF1 silence rescued the effect of MIR503HG siRNA on the two pathways, suggesting that MIR503HG might regulate the MAPK and PI3K/AKT pathways by affecting the expression of TMEFF1, thereby participating in the progression of ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Transmembrane protein with EGF-like and two follistatin like domains 1 (TMEFF1) serves a vital role in the development of various types of tumor, including brain ( 182 ), endometrial carcinoma ( 183 ) and ovarian cancer ( 184 ). Butorphanol significantly inhibits the malignant biological behavior of ES-2 and SKOV3 ovarian cancer cells and the expression of TMEFF1 is significantly downregulated in ovarian cancer cells ( 185 ).…”
Section: Effects Of Opioids On Tumorsmentioning
confidence: 99%